1992
DOI: 10.1093/cvr/26.11.1069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glibenclamide on ventricular arrhythmias and cardiac function in ischaemia and reperfusion in isolated rat heart

Abstract: Glibenclamide may increase the probability of spontaneous termination of ventricular fibrillation and facilitate the restoration of the myocardial function during regional ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…The lack of effect of glibenclamide on reperfusion arrhythmias is in agreement with previous studies in rats (Bernauer, 1997;Ferdinandy et al, 1995). Nevertheless, 1 µM glibenclamide has been reported to reduce the duration of reperfusion ventricular fibrillation in this species (Bril et al, 1992).…”
Section: : Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of effect of glibenclamide on reperfusion arrhythmias is in agreement with previous studies in rats (Bernauer, 1997;Ferdinandy et al, 1995). Nevertheless, 1 µM glibenclamide has been reported to reduce the duration of reperfusion ventricular fibrillation in this species (Bril et al, 1992).…”
Section: : Discussionsupporting
confidence: 92%
“…The lack of effect of glibenclamide on reperfusion arrhythmias is in agreement with previous studies in rats (Bernauer, 1997;Ferdinandy et al, 1995). Nevertheless, 1 µM glibenclamide has been reported to reduce the duration of reperfusion ventricular fibrillation in this species (Bril et al, 1992).Most K ATP openers are pro-arrhythmic during ischaemia (Chi et al, 1990;Wolleben et al, 1989). In agreement, we have previously demonstrated that Ro 31-6930 at relatively high concentration exerted substantial and glibenclamide-sensitive pro-arrhythmic, and action potential shortening, effects during ischaemia (Workman et al, 2000).…”
supporting
confidence: 91%
“…Many Vaughan Williams class I anti-arrhythmic drugs inhibit K ATP channels in cardiac muscles (32)(33)(34). However, some investigators did not find effects of K ATP channel blockers, such as glibenclamide and 5-hydroxydecanoate, on the incidence of arrhythmia after ischemic insult (35)(36)(37). These controversial observations might be due to different experimental conditions or protocols, but it cannot be excluded that the effects of glibenclamide on mitochondrial channels differ in different animal models or conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be mentioned that antiarrhythmic efficacy of insulin-releasing K ATP channel blockers could not be found by a few authors: in acute ischaemia in the rat, glibenclamide did not significantly reduce the incidence of reperfusion arrhythmias (Bril et al 1992;Bernauer 1997). Likewise, in a model with acute ischaemia superimposed on a previous infarction glibenclamide and 5-hydroxydecanoate were ineffective (Chi et al 1989;Friedrichs et al 1996).…”
Section: Discussionmentioning
confidence: 99%